2003
DOI: 10.1515/znc-2003-7-812
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Naphthoquinones from Roots of Lippia microphylla

Abstract: A new prenylated naphthoquinone dimer named microphyllaquinone (1), a mixture of 6-methoxy- and 7-methoxy-naphtho[2,3-b]-furan-4,9-quinones (2a/2b) and tecomaquinone I (3), were isolated from roots of Lippia microphylla. The structures were elucidated by spectroscopic methods, including detailed 1D and 2D (COSY, NOESY, HMQC, HMBC) NMR data. Unpublished 13C NMR data of 2a and 2b are reported. The in vitro cytotoxic activity of the isolated compounds was tested against five types of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Lippia microphylla Cham., popularly known as alecrim-de-tabuleiro, is rarely mentioned in either the phytochemical or pharmacological literature; there are reports of the popular use of its leaves in the treatment of respiratory diseases or as an antiseptic [13]. From the roots of the plant, tecomaquinone I and naphthoquinones have been isolated [14]. These substances displayed significant cytotoxic activity against various cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Lippia microphylla Cham., popularly known as alecrim-de-tabuleiro, is rarely mentioned in either the phytochemical or pharmacological literature; there are reports of the popular use of its leaves in the treatment of respiratory diseases or as an antiseptic [13]. From the roots of the plant, tecomaquinone I and naphthoquinones have been isolated [14]. These substances displayed significant cytotoxic activity against various cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mixture of 5 and 6 was established as 6methoxynaphtho[2,3-b]-furan-4,9-quinone and 7methoxynaphtho[2,3-b]-furan-4,9-quinoneby comparison of its NMR data with the ones in the literature. [15]…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Popularly called as “alecrim-da-chapada,” “alecrim-de-tabuleiro,” “alecrim-pimenta” and “alecrim-do-mato” in the Northeast Brazilian, L. microphylla is a deciduous shrub with a thin and brittle stem (up to 2 m in height), white flowers and with simple and aromatic leaves, which presents serrate margins and evident nerves with no more than 1 cm in length [ 11 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnopharmacological records report the use of L. microphylla leaves to treat gastrointestinal disorders and influenza, bronchitis and sinusitis during vaporization resulting from boiling water. Phytochemical studies revealed the presence of quinones and flavonoids from stem and roots’ ethanol extracts [ 33 , 34 ]. Meanwhile, its aromatic volatile oils extracted by water vapor exhibit an EOs rich in monoterpenes, especially cineole, and terpineol, its more likely active principles.…”
Section: Introductionmentioning
confidence: 99%